Synthesis of acrylonitrile functionalized hydroxymethylfurfural derivatives with Mg(OH)$_{{2}}$ under solvent-free conditions - Mancipe, Sonia; Coca, Valentina; Castillo, Juan-Carlos; Rojas, Hugo; Brijaldo, María Helena; Castañeda, Claudia; Martínez, José Jobanny; Romanelli, Gustavo Pablo (Comptes Rendus. Chimie)
Hydroxymethylfurfural (HMF) derivatives that contain an acrylonitrile group result in interesting scaffold molecules that can be obtained from biomass. However, the synthesis of these types of molecules has not been extensively studied. In this study, we investigated the catalytic activity of Mg(OH)2 and MgO materials. Specifically, we evaluated the Knoevenagel reaction between HMF and malononitrile as a test reaction under solvent-free conditions. The fresh and used catalysts were evaluated using various techniques. Our results indicate that the combination of synthesis methods influences the crystalline, basic, and textural properties of the catalysts. We found that water plays an essential role in obtaining high yields. By using this simple and inexpensive method, we were able to achieve yields near 90% in short reaction times ($<$30 min).